Effects of defendant age and juror bias on judgment of culpability: What happens when a juvenile is tried as an adult? - Tang, Connie M. (American journal of criminal justice, 2003)
The current study examined the possibility that trying juveniles as adults was prejudicial. One hundred and fifty three undergraduate mock jurors, classified as either prosecution-biased (PB) or defense-biased (DB), participated in the experiment. The jurors were randomly assigned to read a murder trial summary depicting a 19-year-old adult defendant (AD-19), a 16-year-old juvenile tried as an adult (JA-16), or a 13-year-old juvenile tried as an adult (JA-13). Defendant age interacted with juror bias. In the JA-16 condition, compared with defense-biased jurors, prosecution-biased jurors found the defendant guilty more often, had higher confidence in the defendant’s guilt, and set a lower standard of proof. By all appearances, some jurors might lose neutrality when judging juveniles tried as adults.